2018
DOI: 10.2298/jas1802217o
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact and determinants of adoption of improved maize production technologies

Abstract: The problem of what production technologies to adopt, and the degree to which farm operations should be improved for attainment of optimum economic benefit have remained undetermined. This study analysed the economics and determinants of adoption of the improved maize (Zea mays) production technology package in Oyo State of Nigeria. A multistage sampling procedure was employed to select one hundred and twenty maize producing farmers for the study in 2016. Data for the study were collected using a structured qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
3
1
0
Order By: Relevance
“…The contact with extension department and participation in their field activities enhanced farmers' awareness of improved maize technologies as the previous research conducted by Mmbando & Baiyegunhi, (2016), found that farmers improved their awareness and adoption of alternative maize cropping technologies by the participation in extension events. The findings of the current study aligned with Obayelu & Ajayi (2018) which depicted that frequent extension contacts increased awareness among farmers and more likely increased the adoption. The frequent contact with extension department also increased awareness of improved maize technologies among farmers these results are similar to Ayinde et al (2010), reported that farmer's social and economic characteristics could impact on farmer's awareness of agricultural innovation.…”
Section: Discussionsupporting
confidence: 86%
“…The contact with extension department and participation in their field activities enhanced farmers' awareness of improved maize technologies as the previous research conducted by Mmbando & Baiyegunhi, (2016), found that farmers improved their awareness and adoption of alternative maize cropping technologies by the participation in extension events. The findings of the current study aligned with Obayelu & Ajayi (2018) which depicted that frequent extension contacts increased awareness among farmers and more likely increased the adoption. The frequent contact with extension department also increased awareness of improved maize technologies among farmers these results are similar to Ayinde et al (2010), reported that farmer's social and economic characteristics could impact on farmer's awareness of agricultural innovation.…”
Section: Discussionsupporting
confidence: 86%
“…Most non-adopters do not follow recommended optimum seed rate (7.5 to 8.7 kg/ha). These results are similar to the study by Obayelu and Ajayi (2018) who noted higher seed costs being incurred by farmers broadcasting sorghum, most of them growing old varieties. Adopters of improved varieties incurred less seed costs probably because most of them obtained free seeds from extension officers and research institutions but also use good agronomic practices.…”
Section: Profitability Of Sorghum Production By Farmerssupporting
confidence: 91%
“…The profitability of production among adopters and non-adopters of improved sorghum varieties was computed by gross margin. The analysis is regarded as the difference between the annual total revenue for each farmer and the variable costs directly associated with them (Obayelu & Ajayi, 2018). The total revenue represents the product of the amount harvested for each farmer and the unit price of sorghum grain.…”
Section: Discussionmentioning
confidence: 99%
“…In case of non-users who faced high seed costs because they used more seeds than the required seed rate (7–10 kg/ha) ( Africa Soil Health Consortium, 2014 ), this is due to non-user farmers broadcasting seeds as planting method but since they hardly follow agronomic advice. Similar study done by Obayelu and Ajayi (2018) who noted that non-user of improved variety incurred high seed cost due to seed broadcasting. Non-users believed that it is easy to maintain unimproved sorghum variety compared to improved sorghum variety.…”
Section: Discussionsupporting
confidence: 68%